The Use of Accounting Information in Financing Decision: The Context of Bangladeshi Private Commercial Banks - Saha, Sumi; Sil, Subhash Chandra; Sayaduzzaman, Md. (Asian Business Review, 2021)
Accounting information is essential to elucidate the financial scenario of any organization. The use of accounting information enhances the decision-making process that has a good role in managerial efficiency. This research study has attempted to know the use of accounting information contained in the annual reports in making a financing decision. Five components of financing decision like selecting the best source of financing,  assessing the cash flows,  preparing the budget and profit planning,  valuation of bond and share as well as financial statement analysis have been considered for the purpose of the study and collected opinions from the selected respondents amounts to one hundred fifty with the use of structured questionnaire and the outcomes of this survey report that the most of the respondents strongly agreed that the accounting information has been used in making a financing decision. The study also reveals that there is a significant relationship among the opinions of the respondents regarding using accounting information in making decisions about the different components of financing decisions.